Menggagas Praktik Kepemimpinan Inklusif di Lembaga Pendidikan Seminari Menengah Santo Paulus Palembang - Murwanto, Petrus; Inharjanto, Anselmus (Sekolah Tinggi Pastoral IPI Malang, 2025)
This study aims to examine the concept of inclusive leadership in educational institutions and to investigate its implementation in seminaries. The research methodology employed was a comprehensive literature review. The findings indicate that inclusive leadership plays a pivotal role in addressing issues of equity, social justice, and diversity by promoting diversity, eradicating oppressive practices, and advancing social justice. Additionally, it is imperative to establish inclusive school environments that embrace and celebrate diversity. The role of inclusive leadership in seminary education is also highlighted. Implementing this leadership model can offer valuable experiences and learning opportunities for seminarians, who will later assume leadership roles and responsibilities within the Church, society, organizations or institutions. Finally, through the practice of inclusive leadership and the emphasis on culturally responsive leadership, educational leaders can contribute to creating inclusive educational environments where all students are acknowledged, valued, and included in the learning process.